2023
DOI: 10.1007/s11695-023-06649-5
|View full text |Cite
|
Sign up to set email alerts
|

Seamguard Buttressing of the Staple Line During Laparoscopic Sleeve Gastrectomy Appears to Decrease the Incidence of Postoperative Bleeding, Leaks, and Reoperations. A Systematic Review and Meta-Analysis of Non-Randomized Comparative Studies

Abstract: Leaks and bleeding are major acute postoperative complications following laparoscopic sleeve gastrectomy (LSG). Various staple line reinforcement (SLR) methods have been invented such as oversewing, omentopexy/gastropexy, gluing, and buttressing. However, many surgeons don't use any type of reinforcement. On the other hand, surgeons who use a reinforcement method are often confused of what kind of reinforcement they should use. No robust and high-quality data supports the use of one reinforcement over the othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…In contrast, a recent meta-analysis demonstrated that only oversewing was an effective method to reduce bleeding and SLC after LSG [ 24 ]. Recent studies have confirmed that both SeamGuard and oversewing could reduce SLC after LSG [ 25 , 26 , 27 ]. Although the use of APM has reduced in recent years [ 28 ], in our institutions, we have continued to use GoR as the only SLR in the period of this study.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, a recent meta-analysis demonstrated that only oversewing was an effective method to reduce bleeding and SLC after LSG [ 24 ]. Recent studies have confirmed that both SeamGuard and oversewing could reduce SLC after LSG [ 25 , 26 , 27 ]. Although the use of APM has reduced in recent years [ 28 ], in our institutions, we have continued to use GoR as the only SLR in the period of this study.…”
Section: Discussionmentioning
confidence: 96%